2020
DOI: 10.21109/kesmas.v15i2.2719
|View full text |Cite
|
Sign up to set email alerts
|

Myths about Menstrual Personal Hygiene among FemaleAdolescents

Abstract: Poor personal hygiene during menstruation among adolescents can lead to urinary tract infection, reproductive tract infection, and skin irritation. This studyaimed to determine the relationship between belief in myths and personal hygiene during menstruation. Cross-sectional quantitative study was conductedusing a sample of 119 10th grade female students from Tangerang 13 State Senior High School selected through purposive sampling. Logistic regressionanalysis was used in this study to determine the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
7
0
3
Order By: Relevance
“…Sikap negatif akan berdampak terhadap perilaku personal hygiene seseorang, seperti halnya kurang memperhatikan kebersihan pada organ genetalia eksternanya. Remaja yang memiliki pemahaman pada personal hygiene menstruasi akan cenderung memiliki kesadaran untuk melakukan tindakan positif saat mereka menstruasi, namun sikap ini dapat berlanjut untuk mendorong perilaku atau berhenti pada sikap saja (Hastuti dkk., 2019;Notoatmodjo, 2012;Palupi, Pristya, & Novirsa, 2020). Oleh karena itu, sangat penting bagi remaja putri mendapatkan pendidikan kesehatan reproduksi sedini mungkin, salah satunya terkait personal hygiene menstruasi.…”
Section: Pendahuluanunclassified
“…Sikap negatif akan berdampak terhadap perilaku personal hygiene seseorang, seperti halnya kurang memperhatikan kebersihan pada organ genetalia eksternanya. Remaja yang memiliki pemahaman pada personal hygiene menstruasi akan cenderung memiliki kesadaran untuk melakukan tindakan positif saat mereka menstruasi, namun sikap ini dapat berlanjut untuk mendorong perilaku atau berhenti pada sikap saja (Hastuti dkk., 2019;Notoatmodjo, 2012;Palupi, Pristya, & Novirsa, 2020). Oleh karena itu, sangat penting bagi remaja putri mendapatkan pendidikan kesehatan reproduksi sedini mungkin, salah satunya terkait personal hygiene menstruasi.…”
Section: Pendahuluanunclassified
“…Total of 16 literatures describe behaviour menstrual hygiene in adolescents in Indonesia. There were 6 literatures (37.5%) that showed behaviour menstrual hygiene poor in adolescents (Amanda and Ariyanti 2020; Azzahra and Adiwiryono 2020; Davis et al 2018;Kartika 2018;Mukarramah 2020;Palupi, Pristya, and Novirsa 2020). 2 literature (12.5%) states that behaviour menstrual hygiene in adolescents is sufficient (Andri, Candra, and Kartika's research (2018) showed that 62.2% of respondents had behaviour vulvar hygiene incorrect during menstruation, including not washing hands before and after performing vulvar hygiene during menstruation, not cleaning the genital organs from front to back, not changing underwear immediately.…”
Section: Description Of Behaviour Menstrual Hygiene In Adolescents In...mentioning
confidence: 99%
“…There are 10 articles that examine attitudes with behaviour menstrual hygiene in adolescents in Indonesia. 8 literature (80%) shows that there is a relationship between attitudes and behaviour menstrual hygiene in adolescents in Indonesia (Amanda and Ariyanti 2020;Kartika 2018;Lestariningsih 2016;Mukarramah 2020;Nurulicha 2019;Palupi, Pristya, and Novirsa 2020;Suryani 2019;Zuraida and Rahmi 2017). 2 literature (20%) states that there is no relationship between attitudes and behaviour menstrual hygiene in adolescents in Indonesia (Azzahra and Adiwiryono 2020;Fitriwati and Arofah 2021).…”
Section: Relationship Of Individual Factors Individualmentioning
confidence: 99%
See 1 more Smart Citation
“…This vaginal infection every year affects women worldwide, almost 10-15% of 100 million women can be caused by improper care for the external genitalia [19]. Adolescents who have an understanding of menstrual personal hygiene will tend to have the awareness to take positive actions when they are menstruating [16], [18], [20]. Therefore, young women need to get reproductive health education as early as possible, one of which is related to menstrual personal hygiene.…”
Section: Introductionmentioning
confidence: 99%